Keberagaman Budaya Yogyakarta Sebagai Destinasi Wisata Budaya Unggulan - Alamsyah, Agung Aldi; Nugraha, Rizki Nurul; Mulya, Muhammad Hafiz; Putra, Eka Syah; Jhanufa, Adam Bina Isyba (Peneliti.net, 2023)
This research was conducted in the city of Yogyakarta by visiting Cultural Tourism objects to find out the cultural diversity of Yogyakarta as a Destination. The focus of this research is to obtain an analysis of the impact that has occurred on the expansion of Yogyakarta's cultural diversity starting from the tourist Attractions of Gamelan, Wayang, Art, Macapat. Then identify leading Cultural Tourism with Tourist Arrivals. This research method uses descriptive research using a qualitative approach that refers to superior cultural Tourist Attractions. And the results of this study conclude that the diversity of tourist destinations in superior cultural Tourist Attractions if managed evenly and the preservation of their culture will have a good impact on the city of Yogyakarta starting from the Economic, Social and Cultural Aspects.